Statistical techniques in business & economics - Lind, Douglas A. (McGraw-Hill/Irwin, 2008)
The new edition of Lind’s Statistical Techniques in Business and Economics is a perennial market best seller due to its comprehensive coverage of statistical concepts and methods delivered in a student-friendly, step-by-step format. The text is non-threatening and presents concepts clearly and succinctly with a conversational writing style. All statistical concepts are illustrated with solved applied examples immediately upon introduction